Thomas Harriot at the National Gallery?. Issue 1 (9th August 2017) - Molaro, P.
Abstract : The English astronomer Thomas Harriot is a shadowy figure. Although an eclectic and brilliant scientist, he seldom published his work. The only picture of him, hanging in the President's room of Trinity College, Oxford, is unconfirmed to this day. In this article, we note a close resemblance between the Trinity College portrait and that of the mathematician in a painting on display at the National Gallery. The sitter is not only a mathematician but also characterized as a cartographer and astronomer as Harriot was. Moreover, the sitter shows certain psychological traits that match Harriot's personality. This association may offer new clues to confirming whether the Trinity College portrait is really of Harriot, and may help lift the veil of mystery from the figure of the first modern British scientist.